The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1680/macr.2008.00016
|View full text |Cite
|
Sign up to set email alerts
|

Axial behaviour of reinforced concrete short columns strengthened with wire rope and T-shaped steel plate units

Abstract: This paper presents a relatively simple column strengthening procedure using unbonded wire rope and T-shaped steel plate units. Twelve strengthened columns and an unstrengthened control column were tested to failure under concentric axial load to explore the significance and shortcomings of the proposed strengthening technique. The main variables investigated were the volume ratio of wire ropes as well as geometrical size and configuration of T-shaped steel plates. Axial load capacity and ductility ratio of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…A study by Yang et al (2011) proved that beams with spiral-type wire ropes developed a higher shear capacity than control beams with closed stirrups, showing that the shear capacity of beams increased with the increase in the number of wire ropes. Yang et al (2009a) proposed a relatively simple column-strengthening procedure using unbonded wire rope and T-shaped steel-plate units. The measured axial load capacities of all strengthened columns were higher than the predictions obtained from ACI 318-05, indicating that the ratio of the measured and predicted values increased with the increase of the volume ratio of wire ropes and flange width of T-shaped steel plates.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Yang et al (2011) proved that beams with spiral-type wire ropes developed a higher shear capacity than control beams with closed stirrups, showing that the shear capacity of beams increased with the increase in the number of wire ropes. Yang et al (2009a) proposed a relatively simple column-strengthening procedure using unbonded wire rope and T-shaped steel-plate units. The measured axial load capacities of all strengthened columns were higher than the predictions obtained from ACI 318-05, indicating that the ratio of the measured and predicted values increased with the increase of the volume ratio of wire ropes and flange width of T-shaped steel plates.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a large number of experimental and analytical studies on the behaviour of the FRP wrapped RC columns under eccentric compression loading have already been conducted (El Maaddawy, 2008a, 2008bHadi & Li, 2004;Hadi, 2006aHadi, , 2006bHadi, , 2007aHadi, , 2007bHadi, , 2009Hu, Wang, & Li, 2011;Pellegrino & Modena, 2010;Quiertant & Clement, 2011;Sadeghian, Rahai, & Ehsani, 2010;Song, Gu, Li, Chen, & Zhang, 2013;Teng, Chen, Smith, & Lam, 2003;Wu, Liu, & Oehlers, 2006). In terms of steel jacketing, extensive experimental and theoretical studies have also been conducted (Adam et al, 2007, Adam, Ivorra, Pallares, Gimenez, & Calderon, 2009a, 2009bCalderón, Adam, Ivorra, Pallarés, & Giménez, 2009;Cirtek, 2001aCirtek, , 2001bFrangou, Pilakoutas, & Dritsos, 1995;Giménez, Adam, Ivorra, Moragues, & Calderón, 2009;Ramirez, 1996;Yang & Ashour, 2007;Yang, Ashour, & Lee, 2009). However, only a few studies involved strengthening these columns by steel jacketing under eccentric compression loading.…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, it has been pointed out that a wrapping method using fibre reinforced plastic (FRP) laminates without flexural stiffness is less effective for square and rectangular columns compared with circular columns. 9,10 Since 2000, the unbonded-type strengthening procedure using no adhesive has become considerably more attractive in various areas for the strengthening of concrete structures. As a result, several interesting investigations have been reported on the unbonded-type strengthening procedure for deficient RC columns.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al 7,10 developed a simple strengthening procedure using unbonded wire rope units and steel elements, and concluded that the wire ropes and steel elements make it possible for the strengthened columns to have a much higher strength gain and ductility ratio than those of conventionally tied columns having the same amount of lateral reinforcement. However, Yang et al 10 also suggested that further research needs to be carried out to examine the seismic performance of columns strengthened with an unbonded-type procedure, because the seismic rehabilitation of concrete structures is significantly dependent on the flexural capacity and ductility of the strengthened columns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation